(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
In this article, the specifics of the banking industry that can influence the applied UX-methods were identified. Based on the identified specifics and expert responses, key factors for selecting UX methods in the banking industry have been identified. In particular, data accuracy, privacy, resource intensity, risk mitigation, and context detection should be emphasized as key criteria for selecting UX methods.